Assessing the Quality of Physical Environments of Early Childhood Schools within the Cape Coast Metropolis in Ghana Using a Sequential Explanatory Mixed-Methods Design - Salome Amissah-Essel; John Elvis Hagan; Thomas Schack (MDPI AG, 2020)
(1) Background: The last few decades have seen researchers giving considerable attention to the physical context of early childhood care and development (ECCD) centers because many of the underlying processes that link physical context are quite similar to psychosocial environmental factors regarding child development. However, research on the physical environments, and the employees' understanding of the importance of physical environments, is often underestimated. The purpose of this study was to assess the quality of the physical environments of ECCD centers in the Cape Coast Metropolis, Ghana, and ascertain whether being a private or public center (center auspices) would be associated with the quality of its physical environment. A further inquiry into the educators' understanding of the importance of physical environment on children's developmental outcomes was made. (2) Methods: Using a sequential explanatory mixed-methods research design, all 160 ECCD centers in the Cape Coast Metropolis were assessed using a modified version of the Children's Physical Environment Rating Scale (CPERS) and a semi-structured interview guide. (3) Results: Descriptive statistics indicated that more than half of the ECCD centers, 56%, rated "fair" on the quality of their physical environment. Although the locations and sites of these centers were of good quality, other physical environmental characteristics (i.e., "Planning of the Centre", "Building as a Whole" and "Outdoor Space") of ECCD centers were also rated to be fair. A Chi-square test showed that center auspices (i.e., being private or public) were not significantly associated with the quality of the physical environments of the centers [χ2(2) = 2.490, p > 0.05], suggesting no significant difference between private and public ECCD centers in terms of the quality of their physical environment. A follow-up qualitative inquiry identified two themes as reasons why play yards in early years' schools were not good: a ''lack of funding" and "governmental support". (4) Conclusions: Our findings suggest that the physical environments of ECCD centers are, to some extent, compromised. Stakeholders (e.g., Ghana Education Service, non-governmental/religious organizations, and private entrepreneurs) should help improve the quality of physical environments and also provide financial assistance for the provision of basic equipment (e.g., learning materials) for private and public ECCD centers in the Cape Coast Metropolis. Educators require in-service training to boost their in-depth understanding of the importance of physical environments on children's developmental outcomes. Future studies could target children's perceptions of their preschools' physical environments as useful empirical information to help guide appropriate policy interventions.